New chaotic satellite image encryption by using some or all the rounds of the AES algorithm - Naim, M.; Ali Pacha, A. (Information security journal., 2023)
This study suggests new satellite chaotic image encryption by using some or all the rounds of the AES algorithm to improve security techniques to protect sensitive data and images during transmission between satellites and ground stations. First, the 7D hyperchaotic system generates the initial key of the pseudo-AES algorithm by using the first and the second variables of the hyperchaotic system. Second, the pseudo-AES algorithm consists of several rounds, where two of them are fixed rounds (the first and the last rounds of the classical AES algorithm), while the number of the remaining rounds depends on the value of the third variable of the hyperchaotic system which considered as a determiner. Third, the permutation operation is applied to the output of the pseudo-AES algorithm by an arrangement permutation on the rows and the columns using the fourth and fifth variables of the hyperchaotic system. Finally, the remaining two variables of the hyperchaotic system are used to generate a mask matrix to be XORed with the output of the previous step to obtain the final cipher image. Moreover, the experimental results show that the proposed technique of encryption for satellite images has extraordinary resistance against well-known attacks.